BALLAST WATER TREATMENT ALTERNATIVES ON BOARD SHIPS - da Rocha Neto, José Lucena; Muniz Santos, Marcelo (Journal of Interdisciplinary Debates, 2021)
Cases of bioinvasion in Brazil and abroad have been causing serious environmental and economic problems of great order. Cases such as the golden mussel, the zebra mussel, and the North Pacific star, among others, caused economic problems in the fishing activity, and in the industry, such as cases of clogging in coolers and maintenance in hydroelectric turbines. The cholera epidemic took place a long time ago, this was also due to the transport of ballast between continents. Onshore ballast water treatments are quite costly and require logistical support. Ballast water treatment on board despite having to change the project, and having physical space in the engine room seems to be an excellent alternative, there are already projects being manufactured, and these have already been approved by the IMO. There is also the alternative of reusing ballast water, through desalination by reverse osmosis, in which fresh water is obtained that can be used for other purposes. The present work aims to demonstrate the problems arising from bioinvasion, and ballast water treatment alternatives, and their advantages.